The coexistence of multiple hydrates triggered by varied H2 molecule occupancy during CO2/H2 hydrate dissociation. (1st January 2023) - Xie, Yan; Zhu, Yu-Jie; Cheng, Li-Wei; Zheng, Tao; Zhong, Jin-Rong; Xiao, Peng; Sun, Chang-Yu; Chen, Guang-Jin; Feng, Jing-Chun
Abstract: The participation of small H2 molecules in hydrate formation generally includes single and multiple occupancy, and the state could vary frequently due to their high fluidity. In this study, distinctly split DSC peaks for hydrate dissociation in constant CO2 /H2 gas phase systems were found, which generally means the coexistence of several hydrates with different phase equilibrium temperatures. Based on the results of hydrate equilibrium decomposition conditions and decomposition enthalpies, we attributed the occurrence of this peculiar phenomenon mainly to different occupation patterns of H2 molecules in hydrate cages. However, several occupancies in the mild conditions of this study may be metastable, which was significantly related to H2 escape. Raman results demonstrated the existence of single occupancy of H2 molecule in both of the 5 12 and 5 1 2 6 2 cages. In addition, co-existing of CO2 and H2 in 5 1 2 6 2 cage may also be detected. The effects of hydrate formation time and morphology on the split DSC peaks further indicated the occupation-related H2 molecule aggregation and probabilistic escape. The discovery in this work may provide some new insights into the deeper understanding of the physical/chemical properties behind clathrate hydrate in the future. Graphical abstract: The different occupation patterns of H2 molecules in hydrate cages. Image 1 Highlights: Splitting DSC peaks for hydrate dissociation in constant CO2 /H2 systems were found. The peculiar phenomenon attributes to the different occupation patterns of H2 molecules in hydrate cages. Several occupancies in mild conditions are metastable which is related to H2 escape. There exists single occupancy of H2 molecule in both of the 5 12 and 5 1, 2 6 2 cages. The co-existing of CO2 and H2 in 5 1, 2 6 2 cage is detected.